Contrasting effects of ischemia on the kinetics of membrane voltage and intracellular calcium transient underlie electrical alternans. - Lakireddy, V; Baweja, P; Syed, A; Bub, G; Boutjdir, M; El-Sherif, N (2005)
Repolarization alternans has been considered a strong marker of electrical instability. The objective of this study was to investigate the hypothesis that ischemia-induced contrasting effects on the kinetics of membrane voltage and intracellular calcium transient (Ca(i)T) can explain the vulnerability of the ischemic heart to repolarization alternans. Ischemia-induced changes in action potential (AP) and Ca(i)T resulting in alternans were investigated in perfused Langendorff guinea pig hearts subjected to 10-15 min of global no-flow ischemia followed by 10-15 min of reperfusion. The heart was stained with 100 microl of rhod-2 AM and 25 microl of RH-237, and AP and Ca(i)T were simultaneously recorded with an optical mapping system of two 16 x 16 photodiode arrays. Ischemia was associated with shortening of AP duration (D) but delayed upstroke, broadening of peak, and slowed decay of Ca(i)T resulting in a significant increase of Ca(i)T-D. The changes in APD were spatially heterogeneous in contrast to a more spatially homogeneous lengthening of Ca(i)T-D. Ca(i)T alternans could be consistently induced with the introduction of a shorter cycle when the upstroke of the AP occurred before complete relaxation of the previous Ca(i)T and generated a reduced Ca(i)T. However, alternans of Ca(i)T was not necessarily associated with alternans of APD, and this was correlated with the degree of spatially heterogeneous shortening of APD. Sites with less shortening of APD developed alternans of both Ca(i)T and APD, whereas sites with greater shortening of APD could develop a similar degree of Ca(i)T alternans but slight or no APD alternans. This resulted in significant spatial dispersion of APD. The study shows that the contrasting effects of ischemia on the duration of AP and Ca(i)T and, in particular, on their spatial distribution explain the vulnerability of ischemic heart to alternans and the increased dispersion of repolarization during alternans.